2013
DOI: 10.1371/journal.pone.0085737
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 (CD138) Modulates Triple-Negative Breast Cancer Stem Cell Properties via Regulation of LRP-6 and IL-6-Mediated STAT3 Signaling

Abstract: Syndecan-1 (CD138), a heparan sulfate proteoglycan, acts as a coreceptor for growth factors and chemokines and is a molecular marker associated with epithelial-mesenchymal transition during development and carcinogenesis. Resistance of Syndecan-1-deficient mice to experimentally-induced tumorigenesis has been linked to altered Wnt-responsive precursor cell pools, suggesting a potential role of Syndecan-1 in breast cancer cell stem function. However, the precise molecular mechanism is still elusive. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 73 publications
12
99
0
2
Order By: Relevance
“…Several in vivo and in vitro models support the idea that syndecan-1 promotes tumorigenesis by promoting Wnt signaling [203], tumor cell adhesion, spreading [230], angiogenesis [231], proliferation [232] and ECM signaling [233]. Recently, Ibrahim et al suggested that syndecan-1 promotes cancer stem cell properties in triple negative breast cancers [234], a factor that negatively impacts cancer therapies. The same study proposed that syndecan promotes stem cell properties via a pathway involving Wnt and IL-6/STAT3 signaling.…”
Section: Syndecans and Their Roles In Breast Cancermentioning
confidence: 99%
“…Several in vivo and in vitro models support the idea that syndecan-1 promotes tumorigenesis by promoting Wnt signaling [203], tumor cell adhesion, spreading [230], angiogenesis [231], proliferation [232] and ECM signaling [233]. Recently, Ibrahim et al suggested that syndecan-1 promotes cancer stem cell properties in triple negative breast cancers [234], a factor that negatively impacts cancer therapies. The same study proposed that syndecan promotes stem cell properties via a pathway involving Wnt and IL-6/STAT3 signaling.…”
Section: Syndecans and Their Roles In Breast Cancermentioning
confidence: 99%
“…Quantitative real-time PCR was conducted in duplicates for each gene of interest using SYBR Green dye and gene expression levels were measured in the step one plus detection System (Applied Biosystems, USA). We used the 2 −ΔΔCt method to analyze data after normalization to 18S ribosomal RNA (rRNA) as previously described [20]. Primer sequences are listed in Supplementary Table 1.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Moreover, the classical co-receptor for growth and angiogenic factors in inflammatory response stimulus CD138 has been described as responsible for linking STAT3, Wnt and NF-ĸB signaling to modulate the BCSC phenotype (77). The self-renewal observed in BCSCs was referred to as being epigenetically regulated in the IL-6-STAT3-phosphatidylinositol 3-kinase (PI3K) pathway (78).…”
Section: Nf-ĸb Signal Transduction Pathway and Bcscsmentioning
confidence: 99%